PENERAPAN DIEGETIC SOUND EFFECT SEBAGAI PEMBANGUN SUSPENSE PADA FILM FIKSI “NGERAKTA” - I Made Ari Artawan; Ni Made Asri Sasmita; Gde Indra Ananta Wijaya; I Kadek Juni Arta (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2026)
This research discusses the application of diegetic sound effects as a key element in building suspense in a fictional film titled “NGERAKTA.” In filmmaking, sound plays a vital role in shaping atmosphere and influencing audience emotions. Diegetic sound refers to audio that originates from within the story world and is recognized by the characters—such as footsteps, creaking doors, or rocking chairs. The film explores local cultural issues and social phenomena, specifically the Kajeng Kliwon ritual and the trend of live streaming, to deliver a moral message about the dangers of pursuing popularity unethically. The research uses a case study with a qualitative approach, covering pre-production, production, and post-production phases. The process includes location surveys, audio breakdown planning, on-location sound recording, and editing with Adobe Audition and Premiere Pro, using techniques such as trimming, noise reduction, equalization, synchronization, and layering. The results show that strategically applied diegetic sound effects significantly enhance the suspense of film scenes, strengthen the audience’s emotional engagement, and enrich the spatial dimensions of the narrative. This study contributes to the field of sound design and supports the development of immersive fiction films with strong moral messages.